Pengaruh Penambahan Kelopak Bunga Rosella Pada Pembuatan Fruit Leather Dari Buah Mangga - Muhammad Nuh (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2018)
Fruits are not always consumed in fresh form. But most are processed into various forms and types of food. This treatment aims in addition to extending the shelf life, as well as to increase the variety of products. Fruits are generally processed into preparations such as jam, jelly, jam, puree, fruit juice, canned fruit, candied dry or wet. One type of dried fruit products other than candied fruits is Fruit leather. Fruit leather is a type of food of fruit flesh that has been destroyed and dried. Drying can be done with drying or it could be with a warming that has a hot temperature of 50-60oC. Fruit leather has a shelf life of up to 12 months, when stored at appropriate storage conditions. In Indonesia, Fruit leather is still not commercially produced. Rossela contains some substances that are very important for health. Including grossy peptin, antochanin, gluside hibiscin, and flavonoids that are useful to prevent cancer, control blood pressure, blood circulation and so forth. The fiber content is high enough that plays a role in launching the exhaust system and lower cholesterol levels in the blood (Erianto, 2009). Based on this background then this study was conducted to combine the mango fruit is known to have high nutritional content with rosella flowers that have some substances that are very important for health. Implementation of Research using Factorial Random Design (RAL), with two main factors that is: Factor I: Varieties of mango fruit (M) consisting of 3 levels: M1: Mango shrimp, M2: sweet sweet Mango, M3: Kueni. Factor II: Addition of rosella (%) of mango flesh, consisting of 4 levels: R1: 40%, R2: 60%, R3: 80%, R4: 100%. The study was conducted with 3 replications. The research was conducted from April to May 2017 at the laboratory of Agricultural Product Technology Faculty of Agriculture UISU Medan. The results showed that the best treatment combination was obtained in Kueni mango with 40% rosella flower meat (M3R1). The strong aroma and taste of Kueni produce the fruit leather with the highest organoleptic value of the color scent. Conversely, the higher percentage of rosella addition resulted in organoleptic assessment of flavor, color and flavor decreased.